Impaired myocardial work in paediatric patients with wolff-parkinson-white syndrome. (4th February 2022) - Borrelli, N; Di Salvo, G; Ciriello, GD; Sabatino, J; Bucciarelli, V; Grimaldi, N; Barracano, R; Fusco, F; Merola, A; Correra, A; Romeo, E; Palma, M; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Wolff-Parkinson-White Syndrome (WPW) has been associated with reduced local myocardium deformation during systole. Left ventricle (LV) dysfunction due to electrical dyssynchrony may require catheter ablation of the accessory pathway, even in asymptomatic patients. Purpose: The study aimed to assess the diagnostic value of non-invasive myocardial work in predicting subtle myocardial abnormalities in patients with WPW. Methods: Forty-four paediatric patients (age 8.2 ± 4.3 years) were included in the study: 12 cases with manifest WPW and 32 age-, sex- and arterial pressure- matched controls (CTR). LV ejection fraction (EF) and global longitudinal strain (GLS) were evaluated. Global myocardial work index (MWI) was measured as the area of the LV pressure-strain loops. From MWI, global Constructive Work (MCW), Wasted Work (MWW) and Work Efficiency (MWE) were estimated. Results: Despite normal LV systolic function by standard echocardiographic parameters, patients with WPW had lower MWI (1233.5 ± 281.6 mmHg% in WPW vs 1624.0 ± 305.8 mmHg% in CTR, p = 0.0004), MCW (1833.4 ± 257.9 mmHg% in WPW vs 2069.0 ± 319.9 mmHg% in CTR, p= 0.03), MWW (187.6 ± 117.7 mmHg% in WPW vs 90.9 ± 58.9 mmHg% in CTR, p= 0.0008) and GWE (90.5 ± 4.8% in WPW vs 95.2 ± 2.2% in CTR, p= 0.00006). There were no significant differences in GLS and EF between patients with WPW and controls. Conclusion: Myocardial work indices were found significantly reduced in patients with WPW, even in presence of normal LV EF and GLS. In patients with WPW, MWI may represent a sensitive measure of myocardial dysfunction and help in the decision-making for catheter ablation.